Revision of the Old World Sobarocephala (Diptera: Clusiidae) - Lonsdale, Owen (Zootaxa, 2014)
The Old World Sobarocephala Czerny, 1903 are revised, with 16 of the 29 known species described here as new: S. anonymos spec. nov., S. apoxys spec. nov., S. cycla spec. nov., S. doryphoros spec. nov., S. insolata spec. nov., S. kapnikos spec. nov., S. laticrinis spec. nov., S. magna spec. nov., S. myllolabis spec. nov., S. nebulosa spec. nov., S. nimbipennis spec. nov., S. orientalis spec. nov., S. paksana spec. nov., S. recava spec. nov., S. secaperas spec. nov., and S. triangula spec. nov. Species are mostly Oriental and Afrotropical in distribution, but species also occur in Japan, Nepal and northern Australia. Species mostly belong to the exclusively Old World S. plumicornis species group, but there are also representatives from the predominantly New World S. flava and S. flaviseta groups. Sobarocephala is described for the first time from Australia, China, Laos, Sri Lanka, Madagascar and West Africa. A key and illustrations are provided.